2018
DOI: 10.1007/s00436-017-5741-2
|View full text |Cite
|
Sign up to set email alerts
|

Experimental infection in Cavia porcellus by infected Amblyomma ovale nymphs with Rickettsia sp. (Atlantic rainforest strain)

Abstract: This study describes experimental infection of guinea pigs (Cavia porcellus) infested with naturally infected Amblyomma ovale nymphs with Rickettsia sp. (Atlantic rainforest strain), and the capacity of A. ovale nymphs to transmit this bacterium. Twenty-six guinea pigs were divided into the following groups: G1, 10 animals infested with uninfected A. ovale nymphs; G2, 10 animals infested with nymphs infected with Rickettsia sp. (Atlantic rainforest strain); and G3, 6 animals without tick infestation. Blood sam… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 29 publications
0
5
0
Order By: Relevance
“…One year later R. parkeri was isolated from Amblyomma ovale ticks collected on a free-roaming domestic dogs in a rural area from Colombia (Londoño et al, 2014). Experimental studies have shown that A. ovale is a reservoir and competent vector of R. parkeri strain Atlantic rainforest (Krawczak et al, 2016;Brustolin et al, 2018). Endemic regions of R. parkeri strain Atlantic rainforest are associated with rural areas, especially areas with vegetation (forest, pastures) where the adult stage of A. ovale attaches to and feeds on dogs, which typically become infested in the forest (Szabó et al, 2013).…”
Section: Discussionmentioning
confidence: 99%
“…One year later R. parkeri was isolated from Amblyomma ovale ticks collected on a free-roaming domestic dogs in a rural area from Colombia (Londoño et al, 2014). Experimental studies have shown that A. ovale is a reservoir and competent vector of R. parkeri strain Atlantic rainforest (Krawczak et al, 2016;Brustolin et al, 2018). Endemic regions of R. parkeri strain Atlantic rainforest are associated with rural areas, especially areas with vegetation (forest, pastures) where the adult stage of A. ovale attaches to and feeds on dogs, which typically become infested in the forest (Szabó et al, 2013).…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, subclinical infection was observed in an additional study that utilized the natural mode of infection of guinea pigs by tick transmission, using A . ovale nymphs infected with the Brazilian Atlantic Rainforest strain [20].…”
Section: Discussionmentioning
confidence: 99%
“…Previous animal model publications, where R . parkeri was used as infectious agent, did not state the biosafety level used [19,20], but it is well accepted that the researchers use this agent at biosafety level 2 containment [21]. The aim of this study was to characterize the pathogenicity of RpARF and describe the clinical course, outcome, pathologic lesions, and anatomic distribution of rickettsiae in this new mouse model of SFG rickettsiosis that can be performed at biosafety level 2.…”
Section: Introductionmentioning
confidence: 99%
“…This strain has a close genetic identity with the Brazilian Atlantic rainforest strain [4] and the Colombian RpARFL isolate [6]. Furthermore, subclinical infection was observed in an additional study that utilized the natural mode of infection of guinea pigs by tick transmission, using A. ovale nymphs infected with the Brazilian Atlantic rainforest strain [17].…”
Section: Discussionmentioning
confidence: 99%